Why Do You Ride?: A Characterization of Mountain Bikers, Their Engagement Methods, and Perceived Links to Mental Health and Well-Being - Roberts, Lisa; Jones, Gareth; Brooks, Rob (Frontiers in Psychology, 2018)
Mountain biking is an increasingly popular outdoor activity on the extreme sport continuum. Extreme and high-risk sports have been investigated using a variety of motivational theories with sensation seeking a dominant theme; however, behavioral and motivational homogeneity within these types of populations should not be assumed. Recent studies have highlighted the therapeutic potential of extreme sports and similar outdoor activities. The aim of this study was to describe the characteristics of mountain biking participants, their engagement methods, and perceived benefits to mental health and wellbeing. This was a cross-sectional survey and participants were recruited via social media. An online questionnaire speciﬁc to the domain of mountain biking was developed. Analysis of the full sample (n=1,484) and of three independent binary sub-samples was conducted using SPSS. The sub-samples compared the results of males and females; younger and older riders; and those who have recently engaged in downhill mountain biking and those who have not. The results have succeeded in identifying some disparities in mountain biker characteristics and engagement methods. The results suggest that some riders found pleasure in higher risk engagement. The study proposes various explanations for the disproportion of women in mountain biking. Irrespective of the confounding factors related to rider characteristics or engagement methods, mountain bikers reported copious benefits to mental health and wellbeing related to their engagement. There was a high reported usage of mountain biking as a coping strategy. As such, this study provides insights that could inform the development of outdoor activities as interventions for mental health.